1991
DOI: 10.1111/j.1365-2621.1991.tb05272.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Volatile Flavor Components in Steamed Rangia Clam by Dynamic Headspace Sampling and Simultaneous Distillation and Extraction

Abstract: The volatile flavor components of steamed rangia clam (Rangia cuneafa) were extracted by dynamic headspace sampling (DHS) and simultaneous distillation/extraction (SDE) techniques, and analyzed by gas chromatography/mass spectrometry (GC/MS) and GC-coupled aroma perception. Twenty-two heterocyclic aroma compounds were identified. Volatile flavor compounds in other chemical classes, such as aldehydes, alcohols, ketones, and terpenes, also were identified. The unique clam aromas were contributed by a combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…This compound has been previously reported as one of the most odorous in mussels 36 and clams. 37 Prost et al 23 showed that (E)-2-penten-1-ol contributed partially to the aroma of farmed turbot. (E)-2-Hexen-1-ol was perceived by six, seven and six judges in extracts of ®sh fed FO, SO and LO diets respectively and exhibits a green and moss-like odour.…”
Section: Olfactometry Analysismentioning
confidence: 98%
“…This compound has been previously reported as one of the most odorous in mussels 36 and clams. 37 Prost et al 23 showed that (E)-2-penten-1-ol contributed partially to the aroma of farmed turbot. (E)-2-Hexen-1-ol was perceived by six, seven and six judges in extracts of ®sh fed FO, SO and LO diets respectively and exhibits a green and moss-like odour.…”
Section: Olfactometry Analysismentioning
confidence: 98%
“…This compound, which is characterised by a cucumber-like odour, has been described as an odorous compound in ®sh and other seafood products. 9,10,15,16,32 According to Milo and Grosch, 36,37 (E,Z)-2,6-nonadienal contributes strongly to the odour of brown trout and cod. Hirano et al 6 described it in ayu as the most important odorous compound, contributing to the cucumber odour of this ®sh.…”
Section: Olfactometry Analysismentioning
confidence: 99%
“…Chemical analysis A 1-L round flask containing each roux sample prepared from 60 g of materials, 440 ml of purified water and 0.5 ml aqueous solution of 0.25 mg/ml internal standard (tridecane or 2,4,6-trimethyl pyridine) was attached to a rotary evaporator (Tanchotikul & Hsieh, 1991). The volatile components from each roux sample (roux 0-V) were collected by steam distillation under reduced pressure (20-24 mm of Hg) at 50˚C for 100 min (Kato, 1992).…”
Section: Methodsmentioning
confidence: 99%